2023
DOI: 10.1186/s13244-023-01440-7
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging for treatment response evaluation and prognostication of hepatocellular carcinoma after thermal ablation

Abstract: Hepatocellular carcinoma (HCC) accounts for the vast majority of primary liver cancer and constitutes a major global health challenge. Tumor ablation with either radiofrequency ablation (RFA) or microwave ablation (MWA) is recommended as a curative-intent treatment for early-stage HCC. Given the widespread use of thermal ablation in routine clinical practice, accurate evaluation of treatment response and patient outcomes has become crucial in optimizing individualized management strategies. Noninvasive imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that patients with tumors demonstrating HBP peritumoral hypointensity had higher recurrence rates after treatment and poorer overall survival than those without peritumoral HBP findings. 58 , 59 Kang et al 60 demonstrated that rate of local tumor progression was higher in patients with HBP peritumoral hypointensity after radiofrequency ablation, likely due to the presence of MVI. 60 , 61 …”
Section: Prognostic Imaging Featuresmentioning
confidence: 99%
“…Previous studies have shown that patients with tumors demonstrating HBP peritumoral hypointensity had higher recurrence rates after treatment and poorer overall survival than those without peritumoral HBP findings. 58 , 59 Kang et al 60 demonstrated that rate of local tumor progression was higher in patients with HBP peritumoral hypointensity after radiofrequency ablation, likely due to the presence of MVI. 60 , 61 …”
Section: Prognostic Imaging Featuresmentioning
confidence: 99%
“…Radiomics, a burgeoning non-invasive diagnostic modality, facilitates dynamic tumor monitoring by mining high-dimensional, quantitative metric features from medical images ( 16 18 ). Its potential shines especially bright in oncology, given the unique hemodynamic and metabolic signatures tumors exhibit ( 19 ). Recent studies underscore the diagnostic and predictive prowess of radiomics, especially when analyzing both tumoral and peritumoral regions in HCC, offering insights into the tumor microenvironment ( 18 , 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Radiomics is a high-throughput "image sequencing" process that derives massive imaging parameters for non-invasive, dynamic detection and quantitative response technology to assess tumor characteristics [13]. Radiomics is widely used in clinical practice, and previous studies have shown that it can be used in the early diagnosis of HCC to assess tumor heterogeneity and microenvironment [14,15].…”
Section: Introductionmentioning
confidence: 99%